Pengaruh Manajemen Krisis Sec Bowl terhadap Reputasi Perusahaan - Suryaningsih, Dewi; Mubarokah, Fina Abiyya Agustin; Rahmat, Vivi Alayda; Alfitra, Musyafa Danish; El Adawiyah, Sadiyah (Innovative: Journal Of Social Science Research, 2025)
Product cleanliness is very important in a country like Indonesia. Therefore, if a crisis issue arises related to the cleanliness of cutlery and cooking utensils on SecBowl products, it could trigger a crisis. This crisis occurred at Secbowl where there was a violation of employee SOPs in the case of washing cutlery and cooking utensils. This case started when an Indonesian influencer (codeblu) who has 1.3 million followers on TikTok started a disclosure about one of the SecBowl places in Kuningan which allegedly washed its cutlery and cooking utensils in the toilet. Therefore, the Secbowl company carried out a series of crisis management. This is then interesting to research, whether this action can affect the company's reputation. With the aim of finding out how much influence the crisis management carried out by Secbowl had on the Company's reputation. This research used quantitative methods and a survey was conducted on 68 respondents and the results showed that the influence of the independent variable on the dependent variable was 24%.